Perlukah Filsafat Ber-Lokalitas-Naratif di Sekolah Dasar? : Membingkai Sekat Pengasuhan Guru - Ria Trisiana; Alfonso Munte; Christine Akuilla Betaubun; Reynhard Malau; Handriantu (Program Studi PGSD Universitas Madako Tolitoli, 2023)
Disparities exist not only in remote area schools, but also in urban schools including international standard schools. Although both have their own challenges through a variety of problems, it does not mean an opportunity for comparing and deciding urban-international schools to be their best elementary schools. Challenges of elementary schools in remote areas, even the authors classify them as remote area localities, which have various limitations, but researchers have to explore the learning treasures of teachers in elementary and junior high schools. Based on qualitative research using interview techniques, the researchers recorded the subject's conversations as a trajectory of the teacher's teaching experience. The purpose of our research to appreciate the pearls of hope and the ins and outs of teachers' empowerment regarding the students' learning life at SDN Penda Pilang and SMPN 1 Atap Kurun, Central Kalimantan through the educational philosophy lens. Results showed that teachers' professionalism could be seen through parenting patterns: translation of responsibility, creation space, care, love, discipline and avoidance of violence.